Atrial Fibrillation in Acute Myocardial Infarction - Bhattarai, Radha; Sayganov, Sergey Anatolevich (Nepalese Heart Journal, 2015)
Background and Aim: New-onset atrial fibrillationfrequently complicates acute myocardial infarction.The incidence ranges from 6 - 21% “1”.We aim todetermine the incidence of atrial fibrillation in thesetting of acute myocardial infarction. Methods: This was a single center prospective study,conducted in the coronary care unit of Saint-PetersburgPokrovskaya city hospital, Russia, during the period,June 2013 to June 2014. Sixty consecutive patientsof acute myocardial infarction with atrial fibrillationwere included in this study. Onset, duration, and modeof termination of atrial fibrillation, clinical factorsassociated with its presentation and its relation withpatient outcome were evaluated. Results: Among the 60 patients 33 (55%) had inferiorwall myocardial infarction and 27 (45%) patientshad anterior wall myocardial infarction. In patientswith inferior wall myocardial infarction the onsetof atrial fibrillation occurred within 24 hours in 30(91%) patients, after 24 hour in 3 (9%) patients. Theepisode lasted for less than 24 hours in 12 (36%), andmore than 24 hours in 21 (64%) patients. In anteriorwall myocardial infarction atrial fibrillation occurredwithin 24 hours in 2 (7%) patients, on the second dayin 25 (93%). The episode lasted less than 24 hoursin 3 (11%), 48 hours in (85%), 72 hours in 1 (4%)patients. There was a significant difference in theonset and duration of atrial fibrillation in relation tothe location of infarction (P < 0.0001). Anterior wallmyocardial infarction was associated with late onsetof atrial fibrillation, increased frequency of heartfailure and higher CCU mortality. Conclusion: The onset of atrial fibrillation in anteriorwall myocardial infarction occurred later and lastedlonger in comparison to inferior wall myocardialinfarction. Increased incidence of heart failure andhigher CCU mortality was associated with anteriorwall myocardial infarction. DOI: http://dx.doi.org/10.3126/njh.v12i1.12327 Nepalese Heart Journal Vol.12(1) 2015: 15-20